Occurrence of tetracyclines and sulfonamides in manures, agricultural soils and crops from different areas in Galicia (NW Spain) - Conde-Cid, Manuel; Álvarez-Esmorís, Cristina; Paradelo-Núñez, Remigio; Nóvoa-Muñoz, Juan Carlos; Arias-Estévez, Manuel; Álvarez-Rodríguez, Esperanza; Fernández-Sanjurjo, María J.; Núñez-Delgado, Avelino (Journal of cleaner production, 2018)
Antibiotics released to the environment are causing public health and sustainability concerns. Taking that into account, we studied the presence of tetracyclines (Tetracycline, Oxytetracycline, Chlortetracycline and Doxycycline) and sulfonamides (Sulfadiazine, Sulfamethazine, Sulfachlorpyridazine and Sulfamethoxypyridazine) in manures, soils and crops from Galicia (Spain), where a high number of cattle, pig and poultry farms exist. We used the HPLC-MS/MS technique to analyze 40 samples of cattle, pig and poultry manure, as well as 65 soil samples, and 27 vegetation samples. The presence of antibiotics was detected in 42% of the manures, 17% of the soils and 44% of crop samples, with maximum concentrations of 106.0 mg kg−1 for individual antibiotics in manures and 0.6 mg kg−1 in soils and plants. The simultaneous presence of several antibiotics was infrequent in soils (only three soils presented two or three antibiotics), and more common in manures and plants, some of them with up to five antibiotics. Pig slurries showed the highest antibiotic concentrations, as well as the highest number of different antibiotics. Crops fertilized with these slurries also showed the highest number of different antibiotics. Antibiotics were detected in 71% of grass and corn samples, and in 33% of wheat grain samples, while they were not detected in potato samples. These results can be very relevant taking into account potential environmental and public health repercussions of antibiotics in soil and water, as well as antibiotics uptake and accumulation in plants, and subsequent incorporation to the food chain. •We studied the occurrence of tetracyclines/sulfonamides in manures, soils and crops.•Antibiotics were detected in 42% of manures, 17% of soils and 44% of crop samples.•Simultaneous presence of antibiotics: infrequent in soil, common in manure and crops.•Pig slurry showed the highest antibiotic concentrations and number of antibiotics.•Antibiotics were detected in 71% of grass/corn, 33% of wheat, 0% of potato samples.